High foliar nitrogen in desert shrubs: An important ecosystem trait or defective desert doctrine? - K.T. Killingbeck; Walter G. Whitford (Ecology, 1996)
Nitrogen concentrations in green and senesced leaves of perennial desert shrubs were compiled from a worldwide literature search to test the validity of the doctrine that desert shrubs produce foliage and leaf litter much richer in nitrogen than that in the foliage of plants from more mesic environments. Mean nitrogen concentration in the green leaves of 78 species of shrubs growing in 11 deserts on five continents (2.2%) was not different from that in 67 species of trees and shrubs growing in deciduous, and mixed deciduous forests (2.2%), and only slightly higher than that in overstory (2.0%) and understory (2.1%) plants growing in tropical wet forest. Mean nitrogen concentration in the green leaves of a ubiquitous shrub that dominates large areas of desert in the United States (Larrea tridentata, 2.1%), and in the green—stem tissues of leafless desert shrubs (2.1%) were also similar to that in plants from mesic environments. Mean green—leaf nitrogen was similar in shrubs growing in different deserts. Mean nitrogen concentration in leaf litter was 1.1% for 11 species of desert shrubs, and 1.0% for the 10 species of this group that were not capable of symbiotic nitrogen fixation. Both concentrations were lower than those routinely provided to describe nitrogen in the litter of desert shrubs (1.5—1.7%), and only slightly higher than the mean nitrogen concentration in 77 species of woody perennials growing in a wide variety of environments worldwide (0.9%). Nitrogen in the leaf litter of one desert shrub (0.4%, Brickellia laciniata) was nearly as low as the lowest leaf—litter nitrogen concentration known for any woody species (0.3%). Because nitrogen concentrations in the foliage of desert shrubs are not higher than those in plants growing in more mesic environments, the tenet that desert shrubs support extraordinarily nitrogen—rich foliage can no longer be supported.
Keywords: desert shrubs; ecosystem traits; green leaves; leaf litter; nitrogen in desert shrubs; nutrient cycling